BERAT BADAN LAHIR RENDAH (BBLR) SEBAGAI FAKTOR RISIKO UTAMA YANG BERHUBUNGAN DENGAN STUNTING PADA ANAK BALITA USIA 24-59 BULAN DI DESA SUKOREJO KECAMATAN GURAH KABUPATEN KEDIRI - Linda Andri Mustofa; Putri Amalia Wahyuningsih (STKIP PGRI Jombang, 2020)
Stunting is a growth failure due to the accumulation of nutritional insufficiency that lasts a long time from pregnancy to 24 months of age and has become a global nutrition problem, especially in poor and developing countries. Indonesia is ranked fifth in the world for the incidence of stunting. The prevalence of children under five with stunting in Kediri Regency is 26.1%. Stunting contributes to infant and toddler morbidity. The purpose of this study was to find the relationship between LBW history and the incidence of stunting in children aged 24-59 months in the village of Sukorejo. The study design used correlational analytic with a retrospective cohort approach. In this study, the independent variable was the history of LBW and the dependent variable was the incidence of stunting. The entire population of children aged 24-59 was 106 with a simple random sampling technique. A sample size of 52 respondents, held on 28-30 July 2020 in Sukorejo Village. The instrument used was secondary data from community reports, and analyzed by using the chi square test. The results showed that a number of 45 (84.6%) had a history of LBW, 6 respondents had a history of LBW stunting. Analysis with the Chi Square test shows that ρvalue = 0.042 <α 0.05, there is a relationship between LBW history and the incidence of stunting in children aged 24-59 months in Sukorejo Village, Gurah District, Kediri Regency. Stunting is a growth failure due to the accumulation of nutritional insufficiency that lasts a long time from pregnancy to 24 months of age. LBW is the dominant factor associated with stunting. Interventions aimed at enhancing the growth and development of children during the early years should consider the factors that trigger LBW.